Constructing the Discourse of Marginalised Ethnic Community in Rai's Fire Cares not its Birthday Anniversary - Rai, Jiwan Kumar (JODEM: Journal of Language and Literature, 2019)
The decade of 2010s is very crucial in literary creation, particularly poetry writing in Nepali literature because the trend of writing shifted to the representation of marginalised people and their “culture as whole way of life” (qtd in During 2).  Mainly the indigenous poets are concerned to the issues of marginalised indigenous people. Bhupal Rai's collection of poem Fire Cares not Its Birthday Anniversary falls in the same trend that deconstructs the cultural discourses of the state power and reconstructs the discourse of the indigenous people. In this context, this study aims to find out the issues of cultural discourses in the poems that the poet resists against and reconstructs a new body of knowledge, i.e. a counter discourse of marginalized. In the same way, it attempts to unfold how he resists against the existing body of cultural discourses and reconstructs the discourses from the perspective of marginalised people. Similarly, this study aims to analyses the logical reasons of redefining and reconstructing the existed ruling groups' body of knowledge. The interpretive method has been used to analyses the texts. For this, Foucault's concept of power/discourse has been applied as a theoretical tool. This research article gives the insights to see the interwoven power relations in social practices and construction of knowledge.